Potencial fisiológico de sementes de milho submetidas a diferentes tratamentos e períodos de armazenamento - Mariucci, Giovanna Emanuelle Gonçalves (2014)
Currently, chemical treatment has been a reality for increasing the potential emergence of seeds, especially for those species of high commercial value, such as hybrid maize. This study aimed to evaluate the seed germination and vigor of maize subjected to different products and storage period. The experimental design was completely randomized in a split plot on time, with four replications. For plot were distributed 9 treatments: an untreated control , one treatment called "standard treatment", which included the addition of fungicide and insecticide. From the standard treatment, six treatments have included various combinations of inoculant, micronutrients and plant growth regulator in order to study the isolated effect of them. Lastly, a treatment called "complete treatment" which included the addition of all products, simulating high investment situation in seed treatment. In subplots the storage periods of 0, 15, 30, 45, 60 and 90 days were evaluated. In each period, the tests were evaluated as follow: first and final count of germination test, modified cold test, germination speed index, final emergence and seedling length. The obtained results permit to be concluded that, seed vigor of maize is reduced by seed treatments, and storage. Micronutrients addition resulted in higher reduction in seeds vigor, regardless of storage time. Treatments did not affect the germination up to 45 days of storage. The treatment with the combinations of fungicide, insecticide and inoculant proved to be feasible, and presented as the most promising seed treatments. It is recommended that the treatment of maize seeds should be carried out as close as possible to the sowing.